Pengaruh Aktivitas Menghafal Al-Qur’an Terhadap Kecerdasaan Spiritual Peserta Didik Kelas X di MA Al-Huda Jatiluhur - sari hodijah; Dede Supendi (Paedagogie: Jurnal Pendidikan dan studi Islam, 2021)
Based on preliminary research conducted at MA Al-Huda regarding the activity of memorizing the Qur'an, temporary information was obtained, namely the existence of a tahfidz Al-Qur'an program carried out by students at MA Al-Huda as an effort to encourage the improvement of the spiritual intelligence of participants. educate. The purpose of this study is to find out how high the spiritual intelligence of students is driven by the activity of memorizing the Qur'an, so it can be said that there is an influence between the activity of memorizing the Qur'an on the spiritual intelligence of students. This research departs from the urgency of education that prioritizes educators who have good morals. The hypothesis in this study is that the more frequent the activity of memorizing the Qur'an, the higher the spiritual intelligence it has. A person who is trained to memorize the Qur'an will experience a very good increase in spiritual intelligence. Because by reciting the holy verses of the Qur'an, we have indirectly established a relationship with Allah, and made the Qur'an a means for dhikr to Allah. This study uses quantitative research methods with correlational methods. For the sampling technique using a saturated sample with a sample of 33 students. As for the technique of data collection is done by means of observation, interviews, and distributing questionnaires with Likert scale measurements. Analysis of the data used is quantitative data by testing the validity and reliability of all instruments and then testing the hypothesis to the level of correlation of the two variables studied. In this study, it was found that a moderate level of correlation between the activity of memorizing the Qur'an had an influence on the spiritual intelligence of students. By getting the results of the effect based on the calculation of the correlation coefficient of 0.254, it means that there is a moderate influence between the activity of memorizing the Qur'an on the spiritual intelligence of students.